Uma extensão à OpenMP para suporte à memória transacional - Jardim, André Desessards (2021)
Submitted by Aline Batista (alinehb.ufpel@gmail.com) on 2021-08-10T19:39:18Z No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Tese_Andre_Jardim.pdf: 1028269 bytes, checksum: d32e1f5a74df6b672804614a373380d7 (MD5)